Use of the “STANDARD G6PDTM” quantitative point-of-care test in neonates and infants - Gornpan Gornsawun; Eh Moo; Klay Htoo; Supalak Chalermvisutkul; Mary Ellen Gilder; Phaw Khu Moo; Laypaw Archusuksan; Taco Jan Prins; Borimas Hanboonkunupakarn; Rose McGready; Francois Nosten; Germana Bancone (PLoS ONE, 2026)
Severe neonatal hyperbilirubinaemia represents a considerable cause of mortality and long term-morbidity in neonates born in low resource settings. Early identification of risk factors, such as glucose-6-phosphate dehydrogenase (G6PD) status, has the potential to prevent severe hyperbilirubinaemia and improve the clinical outcomes. The primary aim of the study was to assess equivalency of cord blood and neonatal capillary blood for diagnosis of G6PD deficiency using the quantitative point-of-care “STANDARD G6PD TM ” test (SD Biosensor, Korea). The secondary aim was to analyse changes in G6PD activity in the first 4 months of life. A total of 75 neonates born in Shoklo Malaria Research Unit (SMRU) clinics were selected based on their G6PD status assessed through routine cord blood screening using the “STANDARD G6PD TM ” test. Using activity thresholds established before in this setting, 25 G6PD deficient, 25 G6PD intermediate and 25 G6PD normal neonates were identified and re-tested using capillary blood collected within 24 hours of life and at day 7 by both “STANDARD G6PD TM ” test and gold standard spectrophotometric assay. They were also followed-up at 1 and 4 months of age to study haematologic and G6PD activity changes over time. The results showed that the “STANDARD G6PD TM ” can be used reliably up to one week of life for testing neonates using the same thresholds established in cord blood. Agreement of G6PD activity measured by the point-of-care test as compared to the gold standard spectrophotometry remained excellent at all sampling time-points. Nevertheless, G6PD activity assessed longitudinally in the same participants decreased over time, both at 1 month of age and at 4 months of age, and interpretation of results in female infants with intermediate activity might require different thresholds. The study demonstrated that the “STANDARD G6PD TM ” can effectively support clinical care in neonates and infants in populations with prevalent G6PD deficiency at the primary care level and especially in low-resource settings.